Oppositional defiant behavior in children with ADHD - Ali, Abdul Haleem (Al-Adab Journal, 2025)
The study of oppositional defiant behavior in children with Attention Deficit Hyperactivity Disorder (ADHD) is critical for several reasons, including that it contributes to accurate diagnosis and differentiation between the disorders. Many of the symptoms of ODD overlap with those of ADHD, such as impulsivity and difficulty following rules, but motivations and behavioral patterns differ, and ADHD symptoms may be associated as one of the strongest predictors of serious antisocial behavior later in life. The current research aimed to identify the following: 1-Identifying oppositional defiant behavior in ADHD children. 2- The significance of the differences in oppositional defiant behavior according to the variables of gender (males and females). To achieve the above, the researcher built a scale of oppositional defiant behavior according to the criteria of the Diagnostic and Statistical Manual of Mental Disorders, fifth edition DSM5, based on the adopted theory of McKinney and Rank 2007, which consisted of a paragraph and five alternatives, and the sample consisted of (100) children in order to extract psychometric properties through the SPSS program. The current research concluded the following results: 1-Children with ADHD have high and statistically significant oppositional defiant behavior. 2- There are statistically significant differences in oppositional defiant behavior according to the gender variable and in favor of males, and there is a statistically significant difference according to age. After that, a set of recommendations and suggestions were made.